THE EFFECT OF GLENOHUMERAL JOINT TRANSLATION AND CODMAN PENDULUM EXERCISES ON THE INCREASE OF GLENOHUMERAL JOINT RANGE OF MOTION IN PATIENTS WITH FROZEN SHOULDER - Sari, Raddya; Syah, Irhas; Sulung, Neila (Prodi Fisioterapi UFDK, 2024)
ABSTRACT Frozen shoulder is the possibility of inflammation, pain, adhesion, atrophy, and capsule shortening. The attacks are generally unilateral, more in women than men and more often in the age of 40-60 years. This type of research is Quasi Experiments with the One Group Pretest and Postest Design research. The independent research variable is the glenohumeral joint and pendular translation exercise while the dependent variable is the analysis of motion of the joint on the frozen shoulder. The sampling technique used purposive sampling with a sample of this study winning 10 respondents. The results of this study prove the fact-average about joint movements before and after the change intervention. The statistical analysis of this study using the Wilcoxon Signed Rank Test obtained different results of flexion motion before and completed intervention 21.1 and p = 0.0001 (p <0.05), extensions with an average difference of 9.8 and p = 0,0001 (p <0.05). The mean with an average of 19.5 and p = 0,0001 (p <0.05), the acceleration with different means is 19.5 and p = 0.0001 (0.05), the addition with the average difference average 2.82 and p = 0.005 (p <0.05), endorotation with a difference in mean of 2.913 and p = 0.004 (p <0.05), exaggeration with an average difference of 2.842 and p = 0.004 (p <0 , 05).Can help improve joint glenohumeral hearing and pendulum codman exercises effective in increasing the motion distribution of glenohumeral joints in patients with frozen shoulder. Keywords : Frozen Shoulder, Range Of Motion , Glenohumeralis Translation Joint, Codman Pendulum Exercise. ABSTRAKFrozen shoulder adalah terjadinya peradangan, nyeri, perlengketan, atropi dan pemendekan kapsul sendi sehingga terjadi keterbatasan sendi bahu. Serangan umumnya bersifat unilateral, lebih banyak pada wanita dibandingkan laki–laki dan lebih sering terjadi pada usia 40–60 tahun.Jenis penelitian ini adalah Quasi Eksperiment dengan pendekatan One Group Pretest and Postest Desain. Variabel independent penelitian ini adalah translasi glenohumeralis joint dan pendular codman exercise sedangkan variabel dependentnya adalah lingkup gerak sendi pada frozen shoulder. Teknik pengambilan sampel menggunakan purposive sampling dengan sampel penelitian ini berjumlah 10 responden. Hasil penelitian ini menunjukkan bahwa rata-rata lingkup gerak sendi sebelum dan sesudah intervensi mengalami perubahan. Analisis statistic penelitian ini menggunakan Wilcoxon Signed Rank Test yang didapat hasil beda rata-rata gerak fleksi sebelum dan sesudah intervensi 21,1 dan p= 0,0001(p<0,05), ekstensi dengan beda rata-rata 9,8 dan p=0,0001(p<0,05). Abduksi dengan beda rata-rata 19,5 dan p= 0,0001(p<0,05), Abduksi dengan beda rata-rata 19,5 dan p=0,0001(0,05), adduksi dengan beda rata-rata 2,82 dan p= 0,005(p<0,05), endorotasi dengan beda rata-rata 2,913 dan p= 0,004(p<0,05), eksorotasi dengan beda rata-rata 2,842 dan p= 0,004(p<0,05). Dapat disimpulkan bahwa pemberian translasi glenohumeralis joint dan pendulum codman exercise efektif terhadap peningkatan lingkup gerak sendi glenohumeralis pada penderita frozen shoulder.Kata Kunci :Frozen Shoulder, Lingkup Gerak Sendi, Translasi Glenohumeralis Joint, Pendulum Codman Exercise.